Human METTL18 is a histidine-specific methyltransferase that targets RPL3 and affects ribosome biogenesis and function. Issue 6 (8th March 2021) - Małecki, Jędrzej M; Odonohue, Marie-Francoise; Kim, Yeji; Jakobsson, Magnus E; Gessa, Luca; Pinto, Rita; Wu, Jie; Davydova, Erna; Moen, Anders; Olsen, Jesper V; Thiede, Bernd; Gleizes, Pierre-Emmanuel; et al.
Abstract: Protein methylation occurs primarily on lysine and arginine, but also on some other residues, such as histidine. METTL18 is the last uncharacterized member of a group of human methyltransferases (MTases) that mainly exert lysine methylation, and here we set out to elucidate its function. We found METTL18 to be a nuclear protein that contains a functional nuclear localization signal and accumulates in nucleoli. Recombinant METTL18 methylated a single protein in nuclear extracts and in isolated ribosomes from METTL18 knockout (KO) cells, identified as 60S ribosomal protein L3 (RPL3). We also performed an RPL3 interactomics screen and identified METTL18 as the most significantly enriched MTase. We found that His-245 in RPL3 carries a 3-methylhistidine (3MH; τ-methylhistidine) modification, which was absent in METTL18 KO cells. In addition, both recombinant and endogenous METTL18 were found to be automethylated at His-154, thus further corroborating METTL18 as a histidine-specific MTase. Finally, METTL18 KO cells displayed altered pre-rRNA processing, decreased polysome formation and codon-specific changes in mRNA translation, indicating that METTL18-mediated methylation of RPL3 is important for optimal ribosome biogenesis and function. In conclusion, we have here established METTL18 as the second human histidine-specific protein MTase, and demonstrated its functional relevance.